Improvement of Wear Resistance of UHMWPE by Adding Solid Lubricating Fillers - Panin S. V. Sergey Viktorovich; Kornienko L. А. Lyudmila; Alexenko V. O. Vladislav; Ivanova L. R. Larisa (Design of Multiscale Composites and Polymers of New Generation, 2016)
Title screen